An open multicenter comparative randomized clinical study on chitosan. Issue 4 (24th June 2015) - Mo, Xiaohui; Cen, John; Gibson, Elaine; Wang, Robin; Percival, Steven L.
ABSTRACT Chitosan, a natural polysaccharide derivate from chitin, offers a promising alternative biomaterial for use in wound dressings. In this work, the safety and efficacy of a next‐generation KA01 chitosan wound dressing in facilitating the healing of nonhealing chronic wounds was studied. This open multicenter comparative prospective randomized clinical study was conducted at three medical centers in China. A total of 90 patients (45 in test group and 45 in control group) with unhealed chronic wounds including pressure ulcers, vascular ulcers, diabetic foot ulcers, and wounds with minor infections, or at risk of infection, were treated with the next generation chitosan wound dressing as the test article or traditional vaseline gauze as a control. Baseline assessments were undertaken with the primary end point being wound area reduction. The secondary end points included pain reduction (using the NRS11 pain scale) at dressing change, wound exudate levels, wound depth and duration of the treatment. After 4 weeks treatment, the wound area reduction was significantly greater in the test group (65.97 ± 4.48%) than the control group (39.95 ± 4.48%). The average pain level in the test group was 1.12 ± 0.23 and 2.30 ± 0.23 in the control group. The wound depth was also lower in the test group 0.30 ± 0.48 cm than the control group 0.54 ± 0.86 cm. The level of exudate fell and the dressing could be removed integrally in both the test and control groups. The mean duration of the test group was 27.31 ± 5.37 days and control group 27.09 ± 6.44 days. No adverse events were reported in either group. In conclusion this open multicenter comparative prospective randomized clinical study has provided compelling evidence that the next generation chitosan wound dressing can enhance wound progression towards healing by facilitating wound reepithelialization and reducing the patients pain level. Furthermore the dressing was shown to be clinically safe and effective in the management of chronic wounds.